A peculiar mixture: German-language cultures and identities in eighteenth-century North America - Stievermann, Jan; Scheiding, Oliver (Pennsylvania State Univ. Press, 2013)
"A collection of essays that explore the transatlantic German cultures and identities of the colonial period"--Provided by publisher
Includes bibliographical references and index
Keywords: North America -- Emigration and immigration -- History -- 18th century; Germany -- Emigration and immigration -- History -- 18th century; Konferenzschrift -- 2009 -- Mainz; Geschichte 1700-1800; Religiöse Identität; Kultur; Ethnische Identität; Deutscher Einwanderer; Nordamerika; Deutsche